Preparation method of residual oil hydrogenation catalyst
During the preparation of the residual oil hydrogenation catalyst, a rotary furnace is used to form a pre-carbon deposit catalyst and mixed with potassium oleate or amine oleate solution, the problem of the catalyst's blocking activity decrease due to carbon deposit is solved, and the stability and efficiency of long-term operation are achieved.
Patent Information
- Application Number
- CN202311272602.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-28
AI Technical Summary
The existing residual oil hydrogenation catalysts are prone to decrease activity due to carbon accumulation and blockage of the pores after a long period of use, resulting in continuous temperature increase to maintain reaction efficiency.
A preparation method is adopted, firstly treating the carrier intermediate through a rotary furnace to form a pre-carbon deposit catalyst at high temperature, and then mixing the pre-carbon deposit catalyst with potassium oleate or amine oleate solution, and then drying to prepare a catalyst with a more stable pore structure.
This method effectively extends the service life of the catalyst, reduces the problem of activity reduction caused by carbon accumulation blockage, and realizes the stability and efficiency of the catalyst in long-term operation.
Smart Images

Figure BDA0004475974830000091 
Figure BDA0004475974830000101 
Figure BDA0004475974830000102
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of residual oil hydrogenation, and particularly relates to a method for preparing a residual oil hydrogenation catalyst. Background Art
[0002] As the current trend of crude oil deterioration continues to intensify, residual oil hydroprocessing technology has received further attention. It is well known that a large amount of impurities in residual oil are easily deposited on the surface of residual oil hydroprocessing catalysts, blocking the channels of catalysts such as demetallization, affecting the demetallization process of residual oil and shortening the service life of the catalyst system. Therefore, a residual oil hydroprocessing catalyst with a macroporous structure is usually provided on the top of the bed to accommodate impurities in the initial residual oil and metal sulfide molecules obtained by demetallization, which plays an important role in the long-term operation of the residual oil hydroprocessing system.
[0003] In recent years, many documents have reported methods for preparing a residue oil hydrogenation catalyst with a high specific surface area and a large pore volume. The commonly used preparation method for obtaining a large pore structure is to mix a carrier material with a pore expander, and treat it at a certain temperature for a period of time under an inert gas atmosphere to obtain a pore-expanding carrier. The pore expander is usually one or a mixture of activated carbon, sodium hydroxide, sodium carbonate, potassium hydroxide, potassium carbonate, etc. CN201510061806.6 discloses a method for preparing a TiO2-containing macroporous residue oil hydrogenation demetallization catalyst. The method is to mix pseudo-boehmite, sesbania powder, a pore expander, a binder and a mixed aqueous solution of nano-titanium hydroxide, shape and roast it into a carrier, impregnate the metal active component and then roast it to obtain a TiO2-containing macroporous residue oil hydrogenation demetallization catalyst. Although the catalyst prepared by adding a pore expander can increase the pore volume and has a higher capacity for impurities such as metals and sulfur in the residue oil raw material, the activity stability of the catalyst during long-term operation and the extension of the catalyst service life still need to be further improved.
[0004] CN201410284778.X discloses a method for preparing a residual oil hydrogenation catalyst, which uses activated coal-based activated carbon and / or graphitized expanded pore blue carbon obtained by pore expansion as a carrier, and then loads active metal sulfides on the carrier as an active component to obtain a catalyst. Compared with alumina carriers, coal-based activated carbon has a high impurity content and is difficult to make high-performance activated carbon, which is difficult to apply to harsh environments. On the other hand, the general disadvantage of expanded pore activated carbon carriers is that their mechanical strength is not high, they wear quickly, and the replacement cost is relatively high. At the same time, with the rise in coal prices, the price advantage of coal-based activated carbon has gradually faded.
[0005] One of the major difficulties in the residue oil hydrogenation reaction is coking. Due to the presence of acidic centers, carbon deposits will gradually form on the catalyst surface. Carbon deposits will reduce the activity of the catalyst because carbon-forming compounds are strongly adsorbed on the acidic centers, covering the active centers, and due to the accumulation of coke, the pores are blocked, so that the reactants cannot approach the active centers for adsorption, which greatly reduces the surface utilization of the catalyst. In the early stage of the reaction, the amount of carbon deposits begins to increase rapidly and the catalyst activity also decreases rapidly. Pre-coked catalysts can be passivated by partial carbonization of the catalyst, which actually slightly reduces the initial catalytic activity and improves the catalytic selectivity and catalytic stability. Although the pre-coked catalyst for residue oil hydrogenation can achieve long-term operation of the reaction to a certain extent, it is inevitable that in the later stage of the reaction, due to excessive carbon deposits blocking the catalyst pores, the activity decreases too much, and the temperature needs to be increased to compensate. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing a residue oil hydrogenation catalyst. The catalyst prepared by the method of the present invention is particularly suitable as a residue oil hydrogenation protective agent. It can be used in the residue oil hydrogenation process to improve the problem of pore blockage in the late reaction of the existing catalyst and the need for continuous temperature increase, thereby achieving long-term operation.
[0007] The present invention provides a method for preparing a residue oil hydrogenation catalyst, comprising:
[0008] (1) preparing a residue oil hydrogenation catalyst carrier;
[0009] (2) preparing an impregnation solution containing active metals and organic oxygen compounds;
[0010] (3) The carrier obtained in step (1) is impregnated in the impregnation solution obtained in step (2), and after curing and drying, the obtained catalyst intermediate is placed in a rotary tube furnace, first purged with an inert gas to maintain a closed inert environment of the furnace, and then the furnace temperature is raised to a treatment temperature of 250-850° C., and treated for 2-6 hours to obtain a pre-carbonized catalyst;
[0011] (4) Mixing the pre-carbonized catalyst obtained in step (3) with a solution of at least one selected from potassium oleate and oleylamine, treating at 70-90° C., and then drying to obtain a catalyst.
[0012] In the present invention, in step (1), the residue oil hydrogenation catalyst carrier can be prepared by conventional methods, for example, the residue oil hydrogenation catalyst carrier material, pore expanding agent and adhesive are mixed, formed, dried and calcined to obtain the carrier.
[0013] In the present invention, the residue oil hydrogenation catalyst carrier material described in step (1) can be a conventional residue oil hydrogenation catalyst carrier material, such as an alumina-based carrier material. Generally, the carrier material is an uncalcined carrier material, such as aluminum hydroxide, or aluminum hydroxide containing conventional additives. Conventional additives can be selected from at least one of silicon, boron, phosphorus, magnesium, etc., and its content accounts for less than 15% of the dry basis mass of the carrier material. Preferably, the properties of the carrier material are as follows: the specific surface area is 100-180m 2 / g, and the pore volume is 0.3-0.5mL / g.
[0014] In the present invention, the pore-enlarging agent in step (1) is preferably a fiber with a length of 1-2 mm and a diameter of 30-50 μm. The amount of the pore-enlarging agent added accounts for 2%-4% of the dry basis weight of the carrier material.
[0015] In the present invention, the binder in step (1) can be a conventional binder, preferably methyl cellulose. The amount of the binder added accounts for 2% to 30% of the dry weight of the carrier material.
[0016] In the present invention, the molding in step (1) can be performed by conventional molding methods, preferably extrusion molding. Conventional molding aids can also be added during the molding process, such as an extrusion aid selected from sesbania powder.
[0017] In the present invention, the drying conditions in step (1) are as follows: temperature is 50-120° C., and time is 1-10 hours.
[0018] In the present invention, the calcination conditions in step (1) are as follows: temperature is 400-700° C., and time is 1-6 hours.
[0019] In the present invention, the pore distribution of the carrier in step (1) is as follows: the pore volume occupied by pores with a pore diameter less than 10 nm is less than 10% of the total pore volume, the pore volume occupied by pores with a pore diameter of 10-35 nm is 45%-70% of the total pore volume, the pore volume occupied by pores with a pore diameter of 35-50 nm is 10%-30% of the total pore volume, and the pore volume occupied by pores with a pore diameter greater than 50 nm is 5%-10% of the total pore volume.
[0020] In the present invention, the active metal in step (2) is selected from at least one of Group VIB metals and Group VIII metals, wherein the Group VIB metal is preferably Mo and / or W, and the Group VIII metal is preferably Co and / or Ni.
[0021] In the present invention, in the impregnation solution of step (2), the concentration of the metal of group VIB in terms of oxide is 2.5%-7.5%, the concentration of the metal of group VIII in terms of oxide is 0.5%-2.5%, and optionally, the concentration of the phosphorus source in terms of P is 2.5%-4.0%. The active metal precursor can be a conventional substance, for example, the molybdenum precursor can be at least one of ammonium molybdate and molybdenum trioxide, the tungsten precursor can be tungstate, the cobalt precursor can be cobalt nitrate, and the nickel precursor can be at least one of nickel nitrate and basic nickel carbonate. The phosphorus source can be phosphoric acid.
[0022] In the present invention, the organic oxygen-containing compound in step (2) is preferably at least one of an organic alcohol and an organic ether, and the carbon number of the organic oxygen-containing compound is 1-3. The organic oxygen-containing compound is preferably at least one of methanol, dimethyl ether, etc. In the impregnation solution, the mass concentration of the organic oxygen-containing compound is 10%-30%.
[0023] In the present invention, the preparation temperature of the impregnation solution in step (2) is 50-85° C., and the pH value is 3-6, which can be adjusted with acid, such as at least one of citric acid and acetic acid.
[0024] In the present invention, the impregnation in step (3) is preferably performed by saturated impregnation.
[0025] In the present invention, in step (3), preferably, the furnace temperature is raised to a first treatment temperature, i.e., 300-480°C, for treatment for 1-3 hours, and then the furnace temperature is raised to a second treatment temperature, i.e., 800-850°C, for treatment for 1-3 hours.
[0026] In the present invention, the initial temperature of the rotary tube furnace is 10°C-30°C, the heating rate is 3-5°C / min, and the temperature is raised to the treatment temperature. The treatment atmosphere is a water vapor atmosphere, wherein the volume ratio of the catalyst intermediate to the water vapor volume in the furnace is 1:(35-50).
[0027] In the present invention, in step (3), preferably, the amount of carbon deposited on the pre-carbon deposited catalyst is 1% to 3% by mass.
[0028] In the present invention, the curing conditions in step (3) are as follows: the temperature is 15-35° C. and the time is 8-15 hours.
[0029] In the present invention, the drying conditions in step (3) are as follows: temperature is 100-200° C., and time is 4-8 hours.
[0030] In the present invention, the inert gas in step (3) may be nitrogen.
[0031] In the present invention, in step (4), the solid-liquid volume ratio of the pre-carbon deposition catalyst obtained in step (3) and a solution of at least one selected from potassium oleate and oleylamine is 1:1-3.
[0032] In the present invention, in step (4), the mass concentration of the solution of at least one selected from potassium oleate and oleylamine is 15%-20%.
[0033] In the present invention, in step (4), the pre-carbonized catalyst obtained in step (3) is mixed with a solution of at least one selected from potassium oleate and oleylamine, and preferably treated at 70-90° C. for 0.5-1.0 h.
[0034] In the present invention, the drying conditions in step (4) are as follows: drying at 50-200° C. for 4-8 hours to obtain a catalyst.
[0035] The present invention also provides a hydrogenation catalyst prepared by the method.
[0036] In the present invention, the catalyst particles are preferably in a four-impeller shape, with a particle size of 2-4 mm.
[0037] In the present invention, the carbon deposit amount of the catalyst is 0.3%-1.5% by mass.
[0038] In the present invention, preferably, the carbon deposit amount of the catalyst is at least 0.2 percentage points lower than the carbon deposit amount of the pre-carbon deposited catalyst, preferably at least 0.8 percentage points lower.
[0039] In the present invention, in the catalyst, based on the mass of the catalyst, the content of the VIB group metal in terms of oxide is 2.5%-7.5%, and the content of the VIII group metal in terms of oxide is 0.5%-2.5%.
[0040] In the present invention, the catalyst is preferably a residual oil hydrogenation protective agent.
[0041] Compared with the prior art, the preparation method of the catalyst of the present invention has the following advantages:
[0042] In the preparation method of the catalyst of the present invention, a catalyst carrier with a specific pore distribution is first prepared, and then a rotary kiln is used to treat the catalyst intermediate. Under high temperature conditions, carbon deposits are formed on the catalyst surface and in the pores. Then, a solution selected from at least one of potassium oleate and oleylamine is used to treat the pre-carbonized catalyst, so that more carbon deposit sites are retained on the inner surface of the catalyst pores, and the carbon deposits on the outer surface of the catalyst are partially removed, so that the carbon deposit content increases from the outside to the inside. In the early stage of the reaction, the outer surface has a relatively higher activity due to relatively less carbon deposits, while the inner surface has a relatively more carbon deposit and a relatively lower activity, so that the carbon deposits formed during the reaction are first formed on the outer surface, and the internal pores remain unobstructed. In the later stage of the reaction, the activity of the outer surface of the catalyst drops sharply, but due to the presence of the mechanical pores, the reaction can still maintain a certain rate on the inner surface to allow the reaction to continue, which is conducive to the long-term operation of the catalyst.
[0043] The catalyst prepared by the method of the present invention is particularly suitable as a residual oil hydrogenation protective agent. When used in the residual oil hydrogenation process, it can improve the problem of pore blockage in the late reaction period of the existing catalyst and the need for continuous temperature increase, thereby achieving long-term operation. DETAILED DESCRIPTION
[0044] The technical solution of the present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited by the embodiments.
[0045] In the present invention, the specific surface area, pore volume and pore distribution are characterized by the BET method, and the instrument is the BSD-PS specific surface area and pore size analyzer. The output pressure during the test is 0.15±0.02MPa; the sample weight is 20-100m 2 The upper limit of sample weighing shall not exceed 2 / 3 of the ball part of the sample tube, and the lower limit shall not be less than 100 mg.
[0046] Example 1
[0047] 145g of alumina powder was selected, 3g of fiber (length 1-2mm, diameter 30-50μm), 3g of sesbania powder, 3g of cellulose, 3g of boric acid, and 180g of water were added, mixed evenly, kneaded, extruded through a 4mm orifice plate four-impeller, dried at 120℃ for 5 hours, and calcined at 600℃ for 3 hours to obtain a carrier. The properties of the carrier material are as follows: specific surface area 141m 2 / g, the pore volume is 0.43mL / g, and the pore distribution is as follows: the pore volume occupied by pores with a diameter of less than 10nm is 8% of the total pore volume, the pore volume occupied by pores with a diameter of 10-35nm is 60% of the total pore volume, the pore volume occupied by pores with a diameter of 35-50nm is 24% of the total pore volume, and the pore volume occupied by pores with a diameter greater than 50nm is 8% of the total pore volume.
[0048] An impregnation solution containing active metals is prepared, with water as solvent, molybdenum trioxide with a MoO3 content of 6.7wt%, basic nickel carbonate with a NiO content of 1.4wt%, and phosphoric acid (concentration 85wt%) with a P content of 3.2%, and the mixture is prepared at 50°C with a pH value of 5, wherein dimethyl ether is added to the impregnation solution at a mass concentration of 12%.
[0049] The carrier was saturated with the impregnation liquid, cured at 25°C for 8 hours and dried at 120°C for 3 hours to obtain a catalyst intermediate, which was placed in a rotary furnace. It was first purged with an inert gas, and then water vapor was introduced at a ratio of 1:40 between the volume of the catalyst intermediate and the volume of water vapor in the furnace body. The furnace temperature was increased to 475°C at a heating rate of 200°C per hour, heated for 1.5 hours, and then increased to 840°C for 1.2 hours to obtain a pre-coked catalyst. The carbon deposition amount of the pre-coked catalyst was 2.4%.
[0050] After the pre-coked catalyst cooled to room temperature, a potassium oleate solution (mass concentration 17%) was selected and heated to 80°C, and the pre-coked catalyst was immersed for 0.5h and dried at 200°C for 6 hours according to the solid-liquid volume ratio of the pre-coked catalyst and the potassium oleate solution being 1:1.5, to obtain catalyst C1.
[0051] The carbon deposit amount of the obtained catalyst was 1.3% by mass.
[0052] The obtained catalyst has a MoO3 mass content of 2.7% and a NiO mass content of 0.8%.
[0053] Example 2
[0054] 145g of alumina powder was selected, 4.5g of fiber (length 1-2mm, diameter 30-50μm), 5g of sesbania powder, 4g of methyl cellulose, 3g of boric acid, and 200g of water were added, mixed evenly, kneaded, extruded through a 4mm orifice plate with four impellers, dried at 120°C for 5 hours, and calcined at 650°C for 3 hours to obtain a carrier. The properties of the carrier material are as follows: the specific surface area is 150m 2 / g, the pore volume is 0.45mL / g, and the pore distribution is as follows: the pore volume occupied by pores with a diameter of less than 10nm is 6% of the total pore volume, the pore volume occupied by pores with a diameter of 10-35nm is 59% of the total pore volume, the pore volume occupied by pores with a diameter of 35-50nm is 28% of the total pore volume, and the pore volume occupied by pores with a diameter greater than 50nm is 7% of the total pore volume.
[0055] An impregnation solution containing active metals is prepared, with water as solvent, molybdenum trioxide with a MoO3 content of 6.0wt%, basic nickel carbonate with a NiO content of 1.2wt%, and phosphoric acid (concentration 85wt%) with a P content of 3.1%, and the mixture is prepared at 50°C with a pH value of 6, wherein methanol with a mass concentration of 28% is added to the impregnation solution.
[0056] The carrier was saturated with the impregnation liquid, cured at 25°C for 8 hours and dried at 120°C for 3 hours to obtain a catalyst intermediate, which was placed in a rotary furnace. It was first purged with an inert gas, and then water vapor was introduced at a ratio of 1:45 between the volume of the catalyst intermediate and the volume of water vapor in the furnace body. The furnace temperature was increased to 405°C at a heating rate of 200°C per hour, heated for 2.0 hours, and then increased to 810°C for 2.0 hours to obtain a pre-coked catalyst. The carbon deposition amount of the pre-coked catalyst was 2.3%.
[0057] After the pre-coked catalyst cooled to room temperature, an oleic acid amine solution (mass concentration 19%) was selected and heated to 80°C, and the pre-coked catalyst was impregnated for 0.5h and dried at 200°C for 6 hours according to the solid-liquid volume ratio of the pre-coked catalyst and the potassium oleate solution of 1:1.5, to obtain catalyst C2.
[0058] The carbon deposit amount of the obtained catalyst was 1.2% by mass.
[0059] The obtained catalyst has a MoO3 mass content of 2.5% and a NiO mass content of 0.7%.
[0060] Example 3
[0061] The carrier and the impregnation liquid are the same as those in Example 1.
[0062] The carrier was saturated with the impregnation liquid, cured at 25°C for 8 hours and dried at 120°C for 3 hours to obtain a catalyst intermediate, which was placed in a rotary furnace. It was first purged with an inert gas, and then water vapor was introduced at a ratio of 1:35 between the volume of the catalyst intermediate and the volume of water vapor in the furnace body, and then the furnace temperature was increased to 475°C at a heating rate of 200°C per hour, heated for 2.5 hours, and then increased to 840°C for 2.8 hours to obtain a pre-coked catalyst. The carbon deposition amount of the pre-coked catalyst was 2.7%.
[0063] After the pre-coked catalyst cooled to room temperature, an oleic acid amine solution (mass concentration 19%) was selected and heated to 80°C, and the pre-coked catalyst was impregnated for 0.5h and dried at 200°C for 6 hours according to the solid-liquid volume ratio of the pre-coked catalyst and the potassium oleate solution of 1:2.0, to obtain catalyst C3.
[0064] The carbon deposit amount of the obtained catalyst was 1.5% by mass.
[0065] The obtained catalyst has a MoO3 mass content of 2.8% and a NiO mass content of 0.9%.
[0066] Comparative Example 1
[0067] Compared with Example 1, the pre-carbon deposited catalyst is used as catalyst DC1.
[0068] 145g of alumina powder was selected, 3g of fiber (length 1-2mm, diameter 30-50μm), 3g of sesbania powder, 3g of cellulose, 3g of boric acid, and 180g of water were added, mixed evenly, kneaded, extruded through a 4mm orifice plate four-impeller, dried at 120℃ for 5 hours, and calcined at 600℃ for 3 hours to obtain a carrier. The properties of the carrier material are as follows: specific surface area 141m 2 / g, the pore volume is 0.43mL / g, and the pore distribution is as follows: the pore volume occupied by pores with a diameter of less than 10nm is 8% of the total pore volume, the pore volume occupied by pores with a diameter of 10-35nm is 60% of the total pore volume, the pore volume occupied by pores with a diameter of 35-50nm is 24% of the total pore volume, and the pore volume occupied by pores with a diameter greater than 50nm is 8% of the total pore volume.
[0069] An impregnation solution containing active metals is prepared, with water as solvent, molybdenum trioxide according to the content of MoO3 of 6.7wt%, basic nickel carbonate according to the content of NiO of 1.4wt%, and phosphoric acid (concentration 85wt%) according to the content of P of 3.2%, mixed at 50°C, and the pH value is 5, wherein dimethyl ether is added to the impregnation solution at a mass concentration of 12%. The carrier is saturated with the impregnation solution, and after curing at 25°C for 8 hours and drying at 120°C for 3 hours, a catalyst intermediate is obtained and placed in a rotary furnace. First, it is purged with inert gas, and then water vapor is introduced at a ratio of 1:40 between the volume of the catalyst intermediate and the volume of water vapor in the furnace body, and the furnace temperature is increased to 475°C at a heating rate of 200°C per hour, heated for 1.5 hours, and then increased to 840°C for 1.2 hours to obtain a pre-coking catalyst DC1. The carbon deposition amount of the pre-coking catalyst is 2.4%.
[0070] Comparative Example 2
[0071] The carrier is the same as in Example 1.
[0072] An impregnation solution containing active metals is prepared, with water as solvent, molybdenum trioxide with a MoO3 content of 6.7wt%, basic nickel carbonate with a NiO content of 1.4wt%, and phosphoric acid (concentration 85wt%) with a P content of 3.2%, mixed at 50°C, with a pH value of 5, and methanol is added to the impregnation solution at a mass concentration of 7%.
[0073] The carrier was saturated with the impregnation liquid, cured at 25°C for 8 hours and dried at 120°C for 3 hours to obtain a catalyst intermediate, which was placed in a rotary furnace. It was first purged with inert gas, and then water vapor was introduced at a ratio of 1:40 between the volume of the catalyst intermediate and the volume of water vapor in the furnace body. The furnace temperature was increased to 475°C at a heating rate of 200°C per hour, heated for 1.0 hour, and then increased to 840°C for 1.0 hour to obtain a pre-carbonized catalyst DC2.
[0074] The carbon deposit amount of the obtained catalyst was 1.3% by mass.
[0075] The obtained catalyst has a MoO3 mass content of 2.7% and a NiO mass content of 0.8%.
[0076] Application Examples
[0077] This example provides a catalyst grading solution for long-term operation of raw materials. The catalysts C1, C2 and C3 of the present invention and the comparative examples DC1 and DC2 and the conventional hydrogenation protective agent FZC-100B are respectively loaded into a fixed bed hydrogenation reactor as protective agents, and then the bed is respectively loaded with a hydrodemetallization catalyst (FZC-204A), a hydrodesulfurization catalyst (FZC-33B) and a hydrodenitrogenation catalyst (FZC-41B) from top to bottom, with a loading volume ratio of 10%: 40%: 25%: 25%. Before the reaction, the catalyst needs to be sulfurized first, and the process is as follows: heat up to 350°C at 10°C / h, and heat at 0.30h. -1 The vacuum distillate oil (VGO) containing dimethyl disulfide (DMDS) was injected into the device at a volume space velocity of 1.0 h / min, wherein the sulfurizing agent was added to ensure that the elemental sulfur content in the vacuum distillate oil accounted for 3% of the total weight, the reaction pressure was 15.7 MPa, the hydrogen-to-oil volume ratio was 758, and the sulfurization time was 40 h. The raw materials treated (see Table 1) were subjected to the following experimental conditions: reaction temperature 385 ° C, hydrogen-to-oil volume ratio 1000, liquid hourly volume space velocity 1.0 h / min -1 , hydrogen partial pressure 14MPa, continuous operation time and corresponding impurity removal effect of generated oil are shown in Table 2.
[0078] Table 1 Raw oil properties
[0079]
[0080]
[0081] Table 2 Evaluation results of catalysts of various examples
[0082]
[0083] It can be seen from the results in Table 2 that the catalyst of the present invention has higher stability and is suitable for long-term operation.
Claims
1. A method for preparing a residual oil hydrogenation catalyst, comprising: (1) preparing a residue oil hydrogenation catalyst carrier; (2) preparing an impregnation solution containing active metals and organic oxygen compounds; (3) The carrier obtained in step (1) is impregnated in the impregnation solution obtained in step (2). After curing and drying, the obtained catalyst intermediate is placed in a rotary tube furnace, first purged with an inert gas to maintain a closed inert environment of the furnace body, and then the furnace temperature is raised to a treatment temperature of 250-850° C., and treated for 2-6 hours to obtain a pre-carbonized catalyst; (4) The pre-carbonized catalyst obtained in step (3) is mixed with a solution of at least one selected from potassium oleate and oleylamine, treated at 70-90° C., and then dried to obtain a catalyst.
2. The preparation method according to claim 1, characterized in that: The residue oil hydrogenation catalyst carrier in step (1) is an alumina-based carrier. Preferably, the properties of the carrier material are as follows: a specific surface area of 100-180 m 2 / g, and the pore volume is 0.3-0.5mL / g.
3. The preparation method according to claim 1 or 2, characterized in that: The pore distribution of the carrier in step (1) is as follows: the pore volume occupied by pores with a pore diameter less than 10 nm is less than 10% of the total pore volume, the pore volume occupied by pores with a pore diameter of 10-35 nm is 45%-70% of the total pore volume, the pore volume occupied by pores with a pore diameter of 35-50 nm is 10%-30% of the total pore volume, and the pore volume occupied by pores with a pore diameter greater than 50 nm is 5%-10% of the total pore volume.
4. The preparation method according to claim 1 or 2, characterized in that: The active metal in step (2) is selected from at least one of Group VIB metals and Group VIII metals, wherein the Group VIB metal is preferably Mo and / or W, and the Group VIII metal is preferably Co and / or Ni.
5. The preparation method according to claim 4, characterized in that: In the impregnation solution of step (2), the concentration of the VIB group metal in terms of oxide is 2.5%-7.5%, the concentration of the VIII group metal in terms of oxide is 0.5%-2.5%, and optionally, the concentration of the phosphorus source in terms of P is 2.5%-4.0%.
6. The preparation method according to claim 1, characterized in that: The organic oxygen-containing compound in step (2) is at least one of an organic alcohol and an organic ether, the carbon number of the organic oxygen-containing compound is preferably 1-3, and is preferably at least one of methanol and dimethyl ether; and / or, in the impregnation solution, the mass concentration of the organic oxygen-containing compound is 10%-30%.
7. The preparation method according to claim 1, characterized in that: The preparation temperature of the impregnation solution in step (2) is 50-85° C., and the pH value is 3-6.
8. The preparation method according to claim 1, characterized in that: The impregnation in step (3) is saturated impregnation; and / or the drying conditions in step (3) are as follows: temperature is 100-200° C., time is 4-8 hours, and curing conditions are as follows: temperature is 15-35° C., time is 8-15 hours.
9. The preparation method according to claim 1, characterized in that: In step (3), the furnace temperature is raised to a first treatment temperature of 300-480° C. for treatment for 1-3 hours, and then the furnace temperature is raised to a second treatment temperature of 800-850° C. for treatment for 1-3 hours.
10. The preparation method according to claim 1 or 9, characterized in that: The treatment atmosphere in step (3) is a water vapor atmosphere, wherein the volume ratio of the catalyst intermediate to the water vapor volume in the furnace body is 1:(35-50).
11. The preparation method according to claim 1, characterized in that: In step (3), the carbon deposition amount of the pre-carbon deposition catalyst is 1%-3% by mass; and / or, in step (4), the carbon deposition amount of the catalyst is 0.3%-1.5% by mass; preferably, the carbon deposition amount of the catalyst is at least 0.2 percentage points lower than the carbon deposition amount of the pre-carbon deposition catalyst, preferably at least 0.8 percentage points lower.
12. The preparation method according to claim 1, characterized in that: In step (4), the mass concentration of the solution of at least one selected from potassium oleate and oleic acid amine is 15%-20%; and / or, the solid-liquid volume ratio of the pre-carbon deposition catalyst obtained in step (3) and the solution of at least one selected from potassium oleate and oleic acid amine is 1:1-3; and / or, the drying conditions in step (4) are as follows: drying at 50-200°C for 4-8 hours to obtain the catalyst.
13. A residue hydrogenation catalyst prepared by the method according to any one of claims 1 to 12.
14. The catalyst according to claim 13, characterized in that The catalyst is a residual oil hydrogenation protective agent. Preferably, based on the mass of the catalyst, the content of the VIB group metal in terms of oxide is 2.5%-7.5%, and the content of the VIII group metal in terms of oxide is 0.5%-2.5%.
Citation Information
Patent Citations
Residual oil hydrogenation catalyst and preparation method thereof
CN104084222A
Macroporous residual oil hydrodemetallization catalyst containing TiO2
CN105983418A
Method for preparing residual oil hydrogenation catalyst, and catalyst
CN102049252A
Hydrogenation catalyst and preparation method thereof
CN106607096A
Residual oil hydrotreating catalyst and preparation method thereof
CN106622267A